The Effectiveness of Using Android-Based Picture Guessing Game in Improving Arabic Vocabulary - Muhammad Rajiv Muwafi; R. Taufiqurrochman (Kitaba, 2023)
In learning a foreign language such as Arabic, vocabulary is a very important aspect. This study discusses an android-based picture guessing game in increasing the Arabic vocabulary of MI Hasyim Asyari Jember students. The purpose of this study was to determine the effectiveness or not of the Android-based picture guessing game in increasing vocabulary. The object is students of class II MI Hasyim Asyari Jember. This research is included in the pre-experimental research because it only uses one class as the experimental class as well as the control class. The design used was one group design pre-test post-test. Researchers used the data method in the form of a test with ten multiple choice questions. Based on the results of the pre test and post test, the average pre test result was 61.5 and the post test average was 83.5. In addition, the calculated t value is greater than t table so that H0 is rejected and Ha is accepted. So, an android-based picture guessing game can be said to be quite effective in increasing the vocabulary of grade II students with a percentage of 65.75%.